Consensus of the Church and Papal Infallibility: A Study in the Background of Vatican I - Costigan, Richard F. (Catholic University of America Press, 2005)
Intro -- Contents -- Acknowledgments -- Abbreviations -- 1. Introduction -- 2. Jacques-Bénigne Bossuet -- 3. Honoré Tournely -- 4. Giuseppe-Agostino Orsi, O.P -- 5. Pietro Ballerini -- 6. Louis Bailly and Nicolas-Sylvestre Bergier -- 7. César-Guillaume La Luzerne -- 8. Alfonso Muzzarelli -- 9. Giovanni Perrone, S.J. -- 10. Conclusion -- Bibliography -- Index.